The portal of the public libraries network of Castilla-la Mancha. Case study - Ventosa Beatty, Ana María; López-Borrull, Alexandre (Revista General de Información y Documentación, 2017)
Since its launch in 2012, the Portal of the Network of Public Libraries of Castilla-La Mancha has been adding sections and services. An evaluation of the service is considered. Two different methodologies are chosen: Evaluation of different parameters and survey among library professionals to consider their position and usefulness. Some of the key findings are the need to incorporate elements of attraction, a subject index and a libraries index, a major update of content and content reorganization and restructuring of the main menu.